2014
DOI: 10.4236/jbise.2014.78060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical Properties of Muscles from Multi-Parametric Magnetic Resonance Imaging

Abstract: We hypothesized that a relationship existed between the mechanical properties and the magnetic resonance imaging (MRI) parameters of muscles, as already demonstrated in cartilaginous tissues. The aim was to develop an indirect evaluation tool of the mechanical properties of degenerated muscles. Leg and arm muscles of adult rabbits were dissected, and tested 12 hours post mortem, in a state of rigor mortis, or 72 hours post mortem, in a state of post-rigor mortis. The tests consisted of a multi-parametric MRI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, T1 and T2 have been shown to correlate with mechanical properties of native and engineered tissues. [ 26,37,38 ] T1, T2, and ADC values were acquired from the samples illustrated in Figure 7 d-f and there was no signifi cant change in any of these parameters over the culture period suggesting that the graft was stable. All of the values for the engineered tissue samples where higher than for native articular cartilage (Table S1, Supporting Information).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Furthermore, T1 and T2 have been shown to correlate with mechanical properties of native and engineered tissues. [ 26,37,38 ] T1, T2, and ADC values were acquired from the samples illustrated in Figure 7 d-f and there was no signifi cant change in any of these parameters over the culture period suggesting that the graft was stable. All of the values for the engineered tissue samples where higher than for native articular cartilage (Table S1, Supporting Information).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…One potential influencing factor is that the hydrogels were much stiffer than values reported for the native human NP of ∼5–25 kPa ( Cloyd et al, 2007 ; Borrelli and Buckley 2020 ) and bovine NP of ∼6–19 kPa ( Recuerda et al, 2011 ; Grenier et al, 2014 ). Notably, Gilchrist et al (2011) demonstrated the importance of both ECM ligands and substrate stiffness on NP phenotype, with a more native NP morphology, enhanced cell-cell interactions, and augmented proteoglycan synthesis when porcine NP cells were cultured on soft (<720 Pa) ECM substrates that contained laminin.…”
Section: Discussionmentioning
confidence: 95%
“…Equivalent experiments were done on intervertebral discs and showed that 45 to 80% of the Young’s modulus, the aggregate modulus, the radial permeability and the axial permeability can be explained mostly by MT and diffusion sequences [60]. On the skeletal muscle, up to 78% of the Young’s modulus can be explained by relaxation times, magnetization transfer and diffusion coefficients suggesting a linear relationship [61]. However, both studies showed changes in the relationships when the tissue is degenerated with a significant modification of the mechanical properties, suggesting that before the use of this technique to quantify the mechanical properties in vivo on patients suffering from various diseases, the relationships have to be defined for each degeneration state of the tissue that mimics the pathology.…”
Section: Discussionmentioning
confidence: 99%